Exploring Izzi's First Language Acquisition: A Case Study of a Five-Year-Old Child - Br Sembiring, Franinta Egia D. R; Rusdi Noor Rosa; Br. Perangin-Angin, Alemina (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2024)
This study examines the first language acquisition of a five-year-old child, focusing on phonological development and the influence of environmental factors. Early language acquisition is essential for children's overall development, yet studies that explore the interplay between phonology and environmental dynamics remain underexplored. This research aims to provide insights into how these elements contribute to a child's linguistic progress. A qualitative descriptive method was employed, with data collected over three weeks through systematic observation and question-and-answer sessions, recorded via video calls. The participant, a boy named Alfahrizi Davin Syahputra Hasibuan, or Izzi, was selected due to his early-stage language development. The findings reveal that Izzi can communicate effectively and comprehend conversations within his environment. Parental involvement and a supportive home setting were identified as key factors in enhancing his phonological development, helping him practice correct pronunciation and build confidence in speech. This study highlights the importance of combining phonological analysis with environmental observations to understand how children acquire language in real-world contexts. The results provide practical implications for parents and educators, suggesting that active engagement and positive interaction can significantly influence children's linguistic abilities and overall communication skills.